Mestariteoksia Guggenheim Museosta. - The Solomon R. Guggenheim Museum, New York (Helsinki : Ateneum - The Fine Arts Academy of Finland, 1994)
Chagall, Marc ; Brancusi, Constantin ; Marc, Franz ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Beckmann, Max ; Moholy-Nagy, Laszlo ; van Doesburg, Theo ; Léger, Fernand ; etc.
Mestariteoksia Guggenheim Museosta / Mästerverk fran Guggenheim Museet, Ateneum, Helsinki, 14.10.1994 - 15.1.1995
boek